Excavation of Myths and Politicizing Communal History in Geetha Hariharan’s in Times of Siege: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Geetha Hariharan, along with Anita Nair, Manju Kapoor, Anita Desai and Kamala Markandaya, contributes a major part in the contemporary Indian literature written in English. She has written novels, short stories and essays over the last three decades. Hariharan made debut in the literary arena with the novel The Thousand Faces of Night which won the Commonwealth Writers Prize for Best First Book in 1993. Her other famous novels are The Ghosts of Vasu Master, When Dreams Travel and Fugitive Histories. Her latest novel is I Have Become the Tide. Hariharan is a social activist trying to change the laws related to the injustice of women. In 1995, Hariharan made a landmark in Indian history by challenging the Hindu Minority and Guardianship Act as discriminatory against women. In Times of Siege was her fourth novel published in 2003. The novel revolves around a number of myths and historical events. It is a typical novel that discusses plainly the growing influence of the ideology of Hinduism in India.